Microsoft Cybersecurity Architect (SC-100) Cert Prep by Microsoft Press. - Press, Microsoft; Pluta, Charles (linkedin.com, 2024)
Prepare for the Microsoft Cybersecurity Architect (SC-100) certification exam. Demonstrate your skills designing and evolving cybersecurity strategy.